Удмурты. Зов языческих предков - Грязев Георгий Геннадьевич (Удмуртия, 2021)
Экземпляры: чз (20220627) / Инвентарный номер: 60263 / Цена: 506.00 / Сис.шифр: 63.5(2) / Авт.знак: У 30 / ГРНТИ: 03.61 / ББК: 63.5(2Рос.Удм)